Medición del Clima Organizacional en una Pyme del Sector Servicios de la Región Centro de Hidalgo (2020)
In recent years, SMEs have increased, mainly those in the service sector, which offer innumerable opportunities to stimulate growth and employment in a country. However, despite the fact that SMEs are the fundamental pillar of modern organizations, their growth has slowed in recent years due to the low productivity they have had. One of the weaknesses of SME managers is not considering their employees as internal customers, they forget that they reflect the company's philosophy, values, quality and service; therefore, they neglect the work environment and employers assume that they provide their employees with the necessary tools to carry out their duties and perform properly. In the present investigation, the study to measure the organizational climate in an SME in the service sector of the state of Hidalgo is proposed, through the application of a questionnaire to its workers, in order to know the perception that they have about the environment that surrounds them in the company. Once the information was processed, alarming results were obtained, which indicated that the company has an organizational climate with a low level, this means that the employees lack motivation, commitment and are not satisfied. Given this analysis, their leaders could implement actions to drive the management of changes in their work environment and manage to plan techniques that influence workers so that there is a feeling of belonging that motivates them to improve their performance and thus increase productivity, services are optimized to be more competitive and the permanence of the company in the market is ensured.